A prontidão para a utilização de recursos tecnológicos no processo de ensino-aprendizagem em Administração o caso Goliat - Bevilacqua, Sólon (2009)
The adoption of new technologies is the study motivation for a great number of marketing authors, such as Parasuraman e Colby (2001) who have developed a methodology called Technology Readiness Index (TRI) to identify the readiness of people to adopt technologic products and services. From the point of view of this methodology, the objective of this research is to identify the readiness of the students / clients of business school of Fucamp in order to adopt the new strategies of learningteaching, specially, a business game. This study has exploratory and descriptive character and by using the Factorial Analisys, it was possible to identify the most important variables to adopt this technology, associated to three dimensions: optimism, inovativeness and readiness. This research indicates the possibility of future studies of casual character, provided of a bigger range in the learning area of business.